IEEE International Conference on Dielectric Liquids, 2005. ICDL 2005.
DOI: 10.1109/icdl.2005.1490035
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of phenol decomposition induced by pulsed corona discharge in water

Abstract: The paper presents the theoretical basis and results of numerical modeling of co-rona discharge phenomenon carried out to determine the value of body force that induces the flow of surrounding fluid. The system of two partial differential equations is solved with the values of electric potential ϕ and space charge density ρq as unknowns. The first equation is of Poisson-type with Laplacian acting on the value of potential and source term dependent on space charge density as well as electric permittivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The reaction of phenol with hydroxyl radicals is very fast, the rate constant being 8.0 · 10 9 M −1 s −1 . Ozone also reacts directly with phenol, however at a much slower rate.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of phenol with hydroxyl radicals is very fast, the rate constant being 8.0 · 10 9 M −1 s −1 . Ozone also reacts directly with phenol, however at a much slower rate.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these reactive species, especially ozone and • OH are the key oxidants. These active species may induce ultraviolet photolysis, electro hydraulic cavitations and supercritical water oxidation that may lead to mineralization . As decrease in the ozone concentration on addition of catalyst was established, it is logical to propose ozone induced radical reactions leading to the formation of OH radicals as shown in Equations .…”
Section: Resultsmentioning
confidence: 99%
“…As decrease in the ozone concentration on addition of catalyst was established, it is logical to propose ozone induced radical reactions leading to the formation of OH radicals as shown in Equations . Also, Dors et al, reported reactions between high energetic electrons present in the discharge streamer and the pollutant molecules in aqueous media that may produce • OH O+normalO2normalO3 normalO3+normalH2O+hv2OH+normalO2 normalO3+normalH2OnormalH2normalO2+normalO2 normalH2normalO2+hv2OH OH+normalH2normalO2normalH2O+HnormalO2 normalH2normalO2+normalO3OH+normalO2+HnormalO2 …”
Section: Resultsmentioning
confidence: 99%
“…For the pulsed high-voltage electrical discharge in liquid, initial models of the bulk-phase corona-induced chemical reactions were reported by M. Dors et al [34]. In that study it was assumed that the pulsed corona discharge leads to the formation of hydrogen peroxide, hydroxyl radicals, and aqueous electrons through reactions (1-3) as shown in Table 1.…”
Section: Mechanism Of Discharge Onlymentioning
confidence: 99%
“…It is commonly believed that the phenol degradation with pulsed high-voltage discharge in aqueous solution shows a first-order kinetics: C = C (0) e (-kt) [7,[10][11][12]. M. Dors et al [34] build a chemical kinetics model of phenol decomposition in water. The densities of the species participating in the chemical reactions were calculated with a set of first order, differential equations describing the chemical conversions.…”
Section: The Kinetics Of Phenol Decompositionmentioning
confidence: 99%